The Risk of Water Erosion on the Foothills of the Middle High Atlas (Morocco): Tagueleft Basin Case Study - Mohamed, Rizki (Journal of natural sciences, life and applied sciences, 2020)
The Tagueleft basin is geographically located in the northern edges of the Middle High Atlas, which is a geomorphological fragile area. The impact of human activity has accelerated water erosion in this mountains area. This is reflected in dynamic and unstable foothills, a decrease in forests density and degradation in the production of the land. On the other hand, land degradation due to human overexploitation of natural resources has increased land degradation in the area.The interest in the risk of erosion on the foothills in the area under study comes in the context of our contribution to clarify the role of geomatical and geomorphological approaches in explaining and identifying the mechanisms responsible for current foothills dynamism through water erosion and its negative impacts on the environment and local development. The aim of the study was to use the EPM (Erosion Potential Méthod) which is formulated by Slobodan Gavrilovic for erosion in mountainous areas and to test the reliability of its results based on fieldwork and remote sensing data.The results of the erosion assessment and its quantification by applying the coefficient (W) for the theoretical model in the area under study have shown that erosion is very important and it touches on wide areas as it appears through the domain classification of the distribution erosion in Tagueleft basin.
Keywords: Middle High Atlas; water erosion; slope dynamics; degradation of fragile environments; remote sensing